Precision Spectroscopy in Astrophysics c - Santos, Nuno C.; Pasquini, Luca.; Correia, Alexandre C. M.; Romaniello, Martino; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2008)
High-accuracy Doppler shift measurements and high-precision spectroscopy are primary techniques in the search for exo-planets. Further extremely interesting applications include the analysis of QSO absorption lines to determine the variability of physical constants and the analysis of the isotopic ratios of absorption lines both in stars and in QSOs, and the determination of stellar oscillations through radial velocity measurements. Since the use of high-precision/resolution spectroscopy is closely connected to the ability to collect a large number of photons, the scientific domains using this technique benefit tremendously from the use of 8-meter class telescopes and will fully exploit the tremendous gain provided by future Extremely Large Telescopes (ELTs). IR high-resolution spectroscopy should soon approach the same accuracy regime achieved in the optical range. This volume comprehensively covers the astrophysical and technical aspects of high-precision spectroscopy with an outlook to future developments, and represents a useful reference work for researchers in those fields.
Part I Abundances and Isotopes -- Part II QSO Absorption Lines -- Part III Fundamental Constants -- Part IV Beyond Photon Noise -- Part V Asteroseismology/Oscillations -- Part VI Planets -- Part VII Future Developments -- Part VIII Posters.
Keywords: Physics; Astronomy; Astrophysics; Cosmology; Observations, Astronomical; Astronomy -- Observations; Optics; Optoelectronics; Plasmons (Physics).; Physics; Astrophysics and Astroparticles; Astronomy, Observations and Techniques; Astronomy, Astrophysics and Cosmology; Optics, Optoelectronics, Plasmonics and Optical Devices; Electronic books